The impact of cation structure upon the acidity of triazolium salts in dimethyl sulfoxide. Issue 1 (20th November 2019) - Konstandaras, Nicholas; Dunn, Michelle H.; Guerry, Max S.; Barnett, Christopher D.; Cole, Marcus L.; Harper, Jason B.
Abstract : The effect of structure on the p K a value of triazolium salts in dimethyl sulfoxide is quantified, considering common structural and electronic motifs. Included is the first p K a measurement of a triazolium salt that generates a mesionic carbene. Abstract : A series of triazolium salts, selected for their varying electronic and steric properties, were prepared and their p K a values were determined in DMSO at 25 °C using the bracketing indicator method. The effect of each systematic structural variation upon the acidity of the triazolium cation has been considered, in particular examining the effects of systematically altering electronic properties, quantified through the use of Hammett σ parameters. The first p K a value for an azolium salt that generates a mesionic carbene is also reported. These new data allow for the selection of appropriate bases for the deprotonation of such triazolium salts and the potential to correlate the p K a values determined herein with the nucleophilicity of the corresponding carbenes.